2022
DOI: 10.1371/journal.pone.0263893
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal opioid overdoses before and after Covid-19: Regional variation in rates of change

Abstract: Background The Covid-19 pandemic and its accompanying public-health orders (PHOs) have led to (potentially countervailing) changes in various risk factors for overdose. To assess whether the net effects of these factors varied geographically, we examined regional variation in the impact of the PHOs on counts of nonfatal overdoses, which have received less attention than fatal overdoses, despite their public health significance. Methods Data were collected from the Overdose Detection Mapping Application Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Overall, the highest plateau was observed in the West Census region, followed in descending order by South, Midwest and Northeast. Variability in these profiles is consistent with recent reports focusing on all opioid overdoses (i.e., not only those due to synthetic opioids), for selected states ( 25 , 26 , 40 ). Future studies could examine the relationship between different relative increases in mortality across regions and States, and diverse public health measures enacted after the onset of COVID-19.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the highest plateau was observed in the West Census region, followed in descending order by South, Midwest and Northeast. Variability in these profiles is consistent with recent reports focusing on all opioid overdoses (i.e., not only those due to synthetic opioids), for selected states ( 25 , 26 , 40 ). Future studies could examine the relationship between different relative increases in mortality across regions and States, and diverse public health measures enacted after the onset of COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Another study reported on the increases in suspected opioid overdoses visits to ED in four states after onset of the COVID-19 lockdowns, ending in August 2020 (5). Other studies have also reported increases in all drug overdoses in individual states and counties in the onset of the COVID-19 pandemic (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Public dashboards, evidence of changes in opioid overdoses, and research using ODMAP as the data source for trend and geospatial analysis are emerging but very limited (Niles et al, 2021;Oneida County Opioid Task Force, 2023;Redford & Dills, 2021). One peer-reviewed paper examined the impact of the COVID-19 stay-at-home orders in the Maryland and DC areas using nonfatal overdoses from ODMAP and found increased nonfatal overdose rates after the orders (Burgess-Hull et al, 2022). Piza et al (2023)…”
Section: Discussionmentioning
confidence: 99%
“…The system's reliance on initial subjective impressions without detailed follow‐up may prove more challenging with the polysubstance nature of the current crisis if the system is expected to quantify specific drug types. One paper indicated that when Maryland's case definition for submitting overdose information to ODMAP changed, ODMAP estimates decreased by approximately 15% (Burgess‐Hull et al., 2022). Although using unconfirmed cases is challenging, it also offers research opportunities to examine differences between initial impressions of LE when encountering a suspected drug overdose compared to the final cause of death determinations—akin to some research on the Drug Evaluation and Classification Program (Beirness et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl and other potent synthetic opioids accounted for the majority of these deaths, consistent with the previously reported trend of increasing incidence of fentanyl-related mortalities from June 2019 to May 2020 (>38.4%) . The COVID-19 pandemic further complicated and exacerbated the opioid public health crisis, as shown by increased rate of fatal and non-fatal overdoses attributed to synthetic opioids alone or in combination with other drugs. Carfentanil is a synthetic opioid that is 80–100× more potent than its parent compound fentanyl and 10,000× more potent than morphine . Both fentanyl and carfentanil were placed in Schedule II of the Controlled Substances Act, meaning that they have “high potential for abuse” and are “considered dangerous” .…”
mentioning
confidence: 99%